Sei sulla pagina 1di 829

Chapter 1

Graphs

1.1 Rectangular Coordinates

1.

0

3.

d =

5 -(-3)

=
=

5 + 3

=

8

= 8

5.

quadrants

 

7.

x

9.

False

11.

(a)

Quadrant II

 
11. (a) Quadrant II  

(b)

Positive x-axis

(c)

Quadrant III

(d)

Quadrant I

(e)

Negative y-axis

(f)

Quadrant IV

13.

The points will be on a vertical line that is two units to the right of the y-axis.

 
13. The points will be on a vertical line that is two units to the right

15.

d(P 1 ,P 2 ) =

(2 - 0) 2 + (1 - 0) 2 = -0) 2 + (1-0) 2 =

2 2 +1 2 = 4 +1 = 5
2 2 +1 2 =
4 +1 =
5
 

17.

d(P 1 ,P 2 ) =

(- 2 - 1) 2 + (2 - 1) 2 = -2 -1) 2 + (2 -1) 2 =

(-3) 2 +1 2 = 9 +1 = 10
(-3) 2 +1 2 =
9 +1 =
10
 

19.

d (P 1 ,P 2 ) =

(5 - 3) 2 + ( 4 - ( - 4) ) 2 - 3) 2 + (4 - (- 4)) 2

=

2 2 + 8 2 = 4 + 64 =
2 2 + 8 2
=
4 + 64 =

68 = 2

17
17

21.

d (P 1 ,P 2 ) =

(6 - ( - 3) ) 2 + (0 - 2) 2 = 6 - (-3)) 2 + (0 - 2) 2 =

9 2 + (-2) 2 = 81 + 4 = 85
9 2 + (-2) 2
=
81 + 4 =
85

Chapter 1

Graphs

23.

d (P 1 ,P 2 ) =

(6 - 4) 2 + ( 4 - ( - 3) ) 2 - 4) 2 + (4 - (-3)) 2

=

2 2 + 7 2 = 4 + 49 = 53
2 2 + 7 2
=
4 + 49 =
53
25. d(P 1 ,P 2 ) = (2.3-(-0.2)) 2 + (1.1-0.3) 2 = (2.5) 2
25.
d(P 1 ,P 2 ) =
(2.3-(-0.2)) 2 + (1.1-0.3) 2 = (2.5) 2 + (0.8) 2
=
6.25 + 0.64 =
6.89
27.
d (P 1 ,P 2 ) =
(0 - a) 2 + (0 - b) 2
=
a 2 + b 2
29.
A =
( -2,5
) ,
B = 1,3 ) ,
(
C =
(
-1,0
)
d(A,B) =
(
1-(-2) ) 2 + (3-5) 2 =
3 2 + (-2) 2
=
9 + 4 =
13
d(B,C) =
(
-1-1 ) 2 + (0 - 3) 2 =
(-2) 2 + (-3) 2
=
4 + 9 =
13
d(A,C) =
(-1-(-2)) 2 + (0- 5) 2 =
1 2 + (-5) 2
=
1 + 25 =
26

Verifying that ? ABC is a right triangle by the Pythagorean Theorem:

31.

[d(A,B)] 2 + [d(B,C)] 2 =[d(A,C)] 2

( 13 ) 2 + ( 13 ) 2 = ( 26 ) 2
(
13 ) 2 +
(
13 ) 2 =
(
26
) 2

13 + 13 = 26 26 = 26

The area of a triangle is A =

2 1 bh. Here,

A = 2 [d(A,B)] [d(B,C)]= 2

1

1 13
1
13

2

13 = 1 13 = 13

2

square units

A =

d(A,B) =

=

d(B,C) =

=

d(A,C) =

=

-5,3

(

) , B = ( 6,0 ) , C = ( 5,5 ) ( 6-
) ,
B =
( 6,0 ) ,
C =
(
5,5
)
(
6- (-5) ) 2 + (0 - 3) 2 =
11 2 + (-3) 2
121 + 9 =
130
(
5- 6 ) 2 + (5- 0) 2 =
(-1) 2 + 5 2
1 + 25 =
26
(5- (-5)) 2 + (5 - 3) 2 =
10 2 + 2 2
100 + 4 =
104
+ 9 = 130 ( 5- 6 ) 2 + (5- 0) 2 = (-1) 2

Section 1.1

Rectangular Coordinates

Verifying that ? ABC is a right triangle by the Pythagorean Theorem:

33.

[d(A,C)] 2 + [d(B,C)] 2 = [d(A,B)] 2

( 104 ) 2 + ( 26 ) 2 = ( 130 ) 2
(
104 ) 2 +
(
26 ) 2 =
(
130
) 2

104 + 26 = 130 130 = 130

The area of a triangle is

1

A = 2 bh. Here,

1

A = 2 d(A,C) ] d(B,C)

[

[

] =

1 1 1 104 26 = 2 2704 = 2 52 = 26 2
1
1
1
104
26 = 2
2704 = 2 52 = 26
2

square units

A =

d(A,B) =

=

d(B,C) =

=

d(A,C) =

=

4,-3

(

) , B = ( 0,-3 ) , C = ( 4,2 ) (0- 4)
) ,
B =
( 0,-3 ) ,
C =
(
4,2
)
(0- 4) 2 + -3-(-3) ) 2 =
(
(-4) 2 + 0 2
16 + 0 =
16 = 4
(
4 -0 ) 2 +
(
2 -(-3) ) 2 =
4 2 + 5 2
16 + 25 =
41
(4 - 4) 2 + (2 -(-3)) 2 =
0 2 + 5 2
0 + 25 =
25 = 5
41 (4 - 4) 2 + (2 -(-3)) 2 = 0 2 + 5 2 0

Verifying that ? ABC is a right triangle by the Pythagorean Theorem:

[d(A,B)] 2 + [d(A,C)] 2 = [d(B,C)] 2

4 2 + 5 2 = ( 41 ) 2 fi 16 + 25 =
4 2 + 5 2 =
(
41 ) 2 fi 16 + 25 = 41 fi 41 = 41
1
The area of a triangle is
A = 2 bh.
Here,
1
1
A = 2 d(A,B) ] d(A,C)
[
[
] =
2 4 5 = 10 square units

35.

All points having an x-coordinate of 2 are of the form (2, y). Those which are 5 units from (–2, –1) are:

(2 -(-2)) 2 + (y - (-1)) 2 = 5 fi 4 2 + (y
(2 -(-2)) 2 + (y - (-1)) 2 = 5 fi
4 2 + (y +1) 2 = 5
Squaring both sides
:
4 2 + (y +1) 2 = 25

37.

16 + y 2 + 2y + 1 = 25

y 2 + 2y -8 = 0

(y + 4)( y - 2) = 0 y = - 4 Therefore, the points are (2, –4) and (2, 2).

or

y = 2

All points on the x-axis are of the form (x, 0). Those which are 5 units from (4, –3) are:

(x - 4) 2 + (0- (-3)) 2 = 5 fi (x - 4) 2
(x - 4) 2 + (0- (-3)) 2 = 5 fi
(x - 4) 2 + 3 2 = 5
Squaring both sides
:
(x - 4) 2 + 9 = 25

Chapter 1

Graphs

39.

41.

43.

45.

47.

49.

x 2 - 8x + 16 + 9 = 25

x 2 -8x = 0 x( x - 8) = 0 x = 0

or

x = 8

Therefore, the points are (0, 0) and (8, 0).

The coordinates of the midpoint are:

Ê x 1 + x 2 , y 1 + y 2 ˆ ˜ = Á

Ë

Ê 5 + 3 , - 4 + 2 ˆ ˜ = Á

Ë

Ë

Ê 2

8 , -2 ˆ

˜

(x,y) = Á

2

2

¯

2

2

¯

2

¯

= (4,-1)

The coordinates of the midpoint are:

(x,y) = Ê Á x 1 + x 2 , y 1 + y 2 ˆ ˜ = Á

Ë

2

2

¯

Ê -3+ 6 , 2 + 0 ˆ ˜ = Á

Ë

Ê 3

Ë 2 , 2 ¯

ˆ

˜

2

2

2

¯

=

ˆ

Ê 3

Á 2 ,1 ˜

Ë

¯

The coordinates of the midpoint are:

(x,y) = Ê Á x 1 + x 2 , y 1 + y 2 ˆ ˜ = Á

Ë

2

2

¯

Ê 4 + 6 , -3+1 ˆ ˜ = Á

Ë

Ë

Ê 10 , -2 ˆ ˜ = (5,-1)

¯

2

2

¯

2

2

The coordinates of the midpoint are:

Ê x 1 + x 2 , y 1 + y 2 ˆ

Ë

Ê -0.2 + 2.3 , 0.3+1.1 ˆ

2

2

Ê 2.1 , 1.4 ˆ

2

2

(x,y) = Á

2

2

˜ = Á

Ë

¯

˜ = Á

¯

Ë

˜ = (1.05, 0.7)

¯

The coordinates of the midpoint are:

Ê x 1 + x 2 , y 1 + y 2 ˆ

Ë

Ê a + 0 , b+ 0 ˆ

2

2

Ê a

b ˆ

˜

(x,y) = Á

2

2

˜ = Á

Ë

¯

˜ = Á

Ë

¯

2 , 2 ¯

The midpoint of AB is:

D =

Ê 0+ 0 , 0 + 6 ˆ

Á

Ë

˜ ¯ = (0, 3)

2

2

The midpoint of AC is: E = Ê 0 + 4 , 0 + 4
The midpoint of AC is:
E =
Ê 0 + 4 , 0 + 4 ˆ
Ë Á
˜
= (2, 2)
2
2
¯
Ê 0+ 4 , 6+ 4 ˆ
The midpoint of BC is:
F =
˜
= (2, 5)
Ë Á
2
2
¯
d(C,D) =
(0 - 4) 2 + (3- 4) 2 =
(-4) 2 + (-1) 2 =
16 +1 =
17
d(B,E) =
( 2 -0 ) 2 + (2 -6) 2 =
2 2 + (-4) 2 =
4 +16 =
20 = 2
5
d(A,F) =
(2 -0) 2 + (5 -0) 2 =
2 2 + 5 2 =
4 + 25 =
29

51.

d(P 1 ,P 2 ) = (-4 -2) 2 + (1-1) 2 = (-6) 2
d(P 1 ,P 2 ) =
(-4 -2) 2 + (1-1) 2 =
(-6) 2 + 0 2 =
36 = 6
d(P 2 ,P 3 ) =
(-4 -(-4)) 2 + (-3-1) 2 =
0 2 + (-4) 2 =
16 = 4
d(P 1 ,P 3 ) =
(-4 -2) 2 + (-3-1) 2 =
(-6) 2 + (-4) 2 =
36 + 16 =
52 = 2
13
Since
[
d(P 1 ,P 2 ) ] 2 + d(P 2 ,P 3 ) ] 2 = d(P 1 ,P 3 )
[
[
] 2 , the triangle is a right triangle.

Section 1.1

Rectangular Coordinates

53.

55.

59.

61.

d(P 1 ,P 2 ) = (0 -(-2)) 2 + (7 -(-1)) 2 = 2
d(P 1 ,P 2 ) =
(0 -(-2)) 2 + (7 -(-1)) 2 =
2 2 + 8 2 =
4 + 64 =
68 = 2
17
d(P 2 ,P 3 ) =
(3-0) 2 + (2- 7) 2 =
3 2 + (-5) 2 =
9 + 25 =
34
d(P 1 ,P 3 ) =
(3-(-2)) 2 + (2 -(-1)) 2 =
5 2 + 3 2 =
25 + 9 =
34

Since d(P 2 ,P 3 ) = d(P 1 ,P 3 ) , the triangle is isosceles.

Since

Therefore, the triangle is an isosceles right triangle.

[

d(P 1 ,P 3 ) ] 2 + d(P 2 ,P 3 ) ] 2 = d(P 1 ,P 2 )

[

[

] 2 , the triangle is also a right triangle.

P 1 = ( 1,3 ) ; P 2 = ( 5,15 ) d (
P 1 =
( 1,3
) ; P 2 =
(
5,15
)
d (
,P 2
)=
(5 -1) 2 + (15 - 3) 2
P 1
=
(
4 ) 2 +
(
12
) 2
=
16 + 144
=
160 = 4
10

57.

P 1 = -4,6 ( ) ; P 2 = ( 4,-8 ) d P
P 1 = -4,6
(
) ; P 2 =
(
4,-8
)
d P 1 ,P 2 ) =
(
(
4 -
(
-4 )) 2 +
(
-8- 6
) 2
= (8) 2 + (-14) 2
= 64 + 196
= 260 = 2
65

Plot the vertices of the square at (0, 0), (0, s), (s, s), and (s, 0).

y (0,s) (s,s) (s,0) x (0,0)
y
(0,s)
(s,s)
(s,0)
x
(0,0)

Find the midpoints of the diagonals.

M 1 = Ê Á 0 + s , 0+ s ˆ

˜

Ê s

= Á

Ë

Ê

= Á

Ë

s

s ˆ

˜

s

˜

Ë

Ê

Á

Ë

2

2

2

0

¯

ˆ

˜

2 , 2 ¯

ˆ

0 + s , s +

2

M 2 =

¯

Since the coordinates of the midpoints are the same, the diagonals of a square intersect at their midpoints.

2 , 2 ¯

Using the Pythagorean Theorem:

90 2 + 90 2 = d 2

8100 + 8100 = d 2

16,200 = d 2 d = 16,200 = 90
16,200 = d 2
d =
16,200 = 90
90 2 + 90 2 = d 2 8100 + 8100 = d 2 16,200 =

2 ª 127.28 feet

90 90 d 90 90
90
90
d
90
90

Chapter 1

Graphs

63.

65.

(a)

First: (90, 0), Second: (90, 90) Third: (0, 90)

y

65. (a) First: (90, 0), Second: (90, 90) Third: (0, 90) y (0,90) (90,90) x (0,0)

(0,90)

(90,90)

(90, 0), Second: (90, 90) Third: (0, 90) y (0,90) (90,90) x (0,0) (90,0) (b) Using

x

(90, 0), Second: (90, 90) Third: (0, 90) y (0,90) (90,90) x (0,0) (90,0) (b) Using

(0,0)

(90,0)

(b) Using the distance formula: d = (310 - 90) 2 + (15 - 90)
(b)
Using the distance formula:
d
=
(310 - 90) 2 + (15 - 90) 2
=
220 2 + (-75) 2
=
54,025 ª 232.4 feet
(c)
Using the distance formula:
d = (300 - 0) 2 + (300 - 90) 2 = 300 2 +
d
=
(300 - 0) 2 + (300 - 90) 2
=
300 2 + 210 2
=
134,100 ª 366.2 feet

The Intrepid heading east moves a distance 30t after t hours. The truck heading south moves a distance 40t after t hours. Their distance apart after t hours is:

d

= (30t) 2 + (40t) 2 = 900t 2 + 1600t 2 = 2500t 2
= (30t) 2 + (40t) 2
= 900t 2 + 1600t 2
= 2500t 2
= 50t

40t

30t d
30t
d

Chapter 1

Graphs

1.2 Graphs of Equations; Circles

1.

add, 4

3.

intercepts

5.

(3,–4)

7.

True

9.

9. 11.

11.

9. 11.

13.

13. 15.

15.

13. 15.

17.

17.  
 

19.

(a)

(–1, 0), (1, 0)

(b)

symmetric with respect to the x-axis, y-axis, and origin

Chapter 1

Graphs

21.

23.

25.

27.

29.

(a)

Ê

Á - p 2 ,0 ˜, Á 2 , 0 ˜, (0,1)

Ë

ˆ

Ê p

¯ Ë

ˆ

¯

(a)

(0, 0)

(a)

(1, 0)

(a)

(–1, 0), (1, 0), (0, –1)

(a)

none

(b)

symmetric with respect to the y-axis

(b)

symmetric with respect to the x-axis

(b)

not symmetric with respect to x-axis, y-axis, or origin

(b)

symmetric with respect to the y-axis

(b)

symmetric with respect to the origin

31.

33.

y = x 4 -

x 0
x
0
 

0

= 0 4 -

1=1 4 -

1
1

0

= 0

1 0

(0, 0) is on the graph of the equation.

 

y 2 = x 2 + 9

 

3 2 = 0 2 + 9

0 2 = 3 2 + 9

 

9 = 9

0 18

(0, 3) is on the graph of the equation.

35. x 2 + y 2 = 4 0 2 + 2 2 = 4
35.
x 2 + y 2 = 4
0 2 + 2 2 = 4
4 = 4
(0, 2) and
(
2,
2

(-2) 2 + 2 2 = 4

8 4

) are on the graph of the equation.

0 = (-1) 4 - -1 0 1- -1
0
= (-1) 4 -
-1
0
1-
-1
0 2 = (-3) 2 + 9 0 18 ( 2 ) 2 + (
0 2 = (-3) 2 + 9
0 18
(
2 ) 2 +
(
2 ) 2 = 4
4 = 4

37.

x 2 = y

 
 

y

- intercept :

Let x = 0,

then 0 2 = y y = 0

(0,0)

x

- intercept :

Let

y = 0,

then

x 2 = 0 x = 0

(0,0)

Test for symmetry:

 
 

x

- axis :

Replace

y by

- y

:

x 2 = - y, which is not equivalent to

x 2 = y.

 

y

- axis :

Replace

x by

- x

:

(- x) 2 = y or x 2 = y, which is equivalent to

x 2 = y.

Origin :

Replace

x by

- x

and y by

- y

:

(- x) 2 = -y or x 2 = -y,

which is not equivalent to

x 2 = y.

Therefore, the graph is symmetric with respect to the y - axis .

39.

y = 3x

y

- intercept :

Let

x = 0,

then y = 3

(0,0)

x

- intercept :

Let

y = 0,

0 = 0 x = 0

then 3 x = 0

(0,0)

Section 1.2

Graphs of Equations; Circles

Test for symmetry:

x

- axis :

Replace

y by

-

y

:

- y = 3x, which is not equivalent to

y = 3 x.

y

- axis :

Replace

x by

- x

:

y = 3(- x ) or y = -3x,

 

which is not equivalent to

 

y = 3x.

Origin :

Replace x by - x and y by which is equivalent to

- y

- y = 3(- x) or y = 3x, y = 3 x.

:

 

Therefore, the graph is symmetric with respect to the origin.

41.

x 2 + y - 9 = 0

y

- intercept :

Let

x = 0,

then 0 + y - 9 = 0 y = 9

x

- intercept :

Let

y = 0,

then

x 2 - 9 = 0 x = ±3

(0,9)

(-3,0),(3,0)

Test for symmetry:

x - axis :

Replace y by

- y

:

x 2 + (-y)- 9 = 0 or x 2 - y - 9 = 0,

which is not equivalent to

x 2 + y -9 = 0.

y - axis :

Replace x by -

x : (- x) 2 + y - 9 = 0 or x 2 + y -9 = 0,

which is equivalent to

x 2 + y -9 = 0.

Origin :

Replace x by

- x

and y by

- y

:

(- x) 2 + (-y)- 9 = 0 or x 2 - y -9 = 0,

which is not equivalent to

x 2 + y - 9 = 0.

Therefore, the graph is symmetric with respect to the y-axis.

43.

9 x 2 + 4 y 2 = 36

y

- intercept : Let

x = 0,

then

x

- intercept :

Let

y = 0,

then

4 y 2 = 36 y 2 = 9

9x 2 = 36 x 2 = 4

y

= ±3

(0,-3),(0,3)

x

= ±2

(-2,0),(2,0)

Test for symmetry:

x - axis :

Replace y by

:

9 x 2 + 4(-y) 2 = 36 or 9x 2 + 4y 2 = 36,

9 x 2 + 4y 2 = 36.

- y

which is equivalent to

y - axis :

Replace x by

- x

:

9(-x ) 2 + 4y 2 = 36 or 9x 2 + 4y 2 = 36,

which is equivalent to

9 x 2 + 4y 2 = 36.

Origin :

Replace x by - x and y by

- y

:

9(- x) 2

+ 4(-y) 2 = 36 or 9 x 2 + 4y 2 = 36,

which is equivalent to

9 x 2 + 4y 2 = 36.

Therefore, the graph is symmetric with respect to the x-axis, the y-axis, and the origin.

45.

y = x 3 - 27

y

- intercept :

Let

x

= 0,

then

y

= 0 3 - 27 y

= -27

(0,-27)

x

- intercept :

Let

y = 0,

then

0 = x 3 - 27 x 3 = 27 x = 3

(3,0)

Chapter 1

Graphs

Test for symmetry:

x

- axis :

Replace

y by

-

y

:

- y = x 3 - 27, which is not equivalent to

y = x 3 - 27.

y

- axis :

Replace

x

by

-

x

:

y = (-

x) 3

- 27

or y = -x 3 - 27,

 

which is not equivalent to

 

y = x 3 - 27.

Origin :

Replace x by - x and y by

- y

:

- y = (- x) 3 - 27 or

y = x 3 + 27, which is not equivalent to

y = x 3 - 27.

Therefore, the graph is not symmetric with respect to the x-axis, the y-axis, or the origin.

47.

y = x 2 - 3x - 4

 

y

- intercept :

Let

x

= 0,

then

y = 0 2 - 3(0) - 4 y = -4

(0,-4)

x

- intercept :

Let

y

= 0,

then

0 = x 2 - 3x - 4 ( x - 4)( x +1) = 0 x = 4, x = -1

(4,0), (-1,0)

Test for symmetry:

 
 

x

- axis :

Replace

y by

- y

:

- y = x 2 - 3x - 4, which is not

 
 

equivalent to

y = x 2 - 3x - 4.

 

y

- axis :

Replace x by -

x

:

y = (- x) 2 - 3(-x) - 4

or y = x 2 + 3x - 4,

 
 

which is not equivalent to

y = x 2 - 3x - 4.

 

Origin :

Replace x by

- x

and y by

- y

:

- y = (- x) 2 - 3(-x) - 4 or

 
 

y = -x 2 - 3 x + 4, which is not equivalent to

y = x 2 - 3x - 4.

 

Therefore, the graph is not symmetric with respect to the x-axis, the y-axis, or the origin.

 

3x

49.

y =

x 2 + 9

y

- intercept :

Let

x

= 0,

x

- intercept :

Let

y

= 0,

Test for symmetry:

 
 

x

- axis :

Replace

y by

then y =

then 0 =

+ 0 9 = 0

0

(0,0)

3x 9 3x = 0 x = 0 x 2 +

- y

:

- y =

3x + 9 , which is not x 2

(0, 0)

y - axis :

Origin :

equivalent to

Replace x by

- x

:

3x

y =

y =

x 2 + 9 .

3(-x)

(

-x

) 2 +

9

which is not equivalent to

or y =

-3x

x 2 + 9 ,

y =

3x

x 2 + 9 .

Replace x by

- x

and y by

- y

:

- y =

y =

3x + 9 , which is equivalent to x 2

-3x

(-x) 2 + 9 or

y =

3x

x 2 + 9 .

Therefore, the graph is symmetric with respect to the origin.

Section 1.2

Graphs of Equations; Circles

51.

y =

-x 3

x 2 -9

y

- intercept :

Let x = 0,

then

0

y = -9 = 0

(0,0)

x

- intercept :

Let y = 0,

Test for symmetry:

then 0 =

3

-x -9 fi -x 3 = 0 x = 0

x 2

(0,0)

x - axis :

y - axis :

Replace

y by

-

y :

Replace

x by

- x :

- y =

3

-x -9 , which is not equivalent to x 2

y =

-(-x) 3

(-x) 2 - 9

or y =

x 3

x 2 -9 ,

Origin :

which is not equivalent to

Replace x by

- x

and y by

- y :

-x 3

y =

- y =

x 2 -9 . -(-x)

3

(-x) 2

-9 or

-

y =

x 3 9 , which is equivalent to x 2 -

y =

-x 3

x 2 -9 .

y =

-x 3

x 2 -9 .

Therefore, the graph is symmetric with respect to the origin.

53.

57.

y = x 3

y = x 3

55.

x
x

y =

x y =

y = 3x + 5

59.

2 x + 3 y = 6

2 = 3a + 5 3a = - 3 a = -1

2a+ 3b = 6 b = 2- 2

3 a

Chapter 1

Graphs

61.

Center = (2, 1)

 

63.

Radius = distance from (0, 1) to (2,1)

 

= (2 -0) 2 + (1-1) 2

 
 
= 4 = 2

= 4 = 2

 

(x - 2) 2 + (y -1) 2

= 4

65.

( x - h) 2 + (y - k) 2

= r 2

 

(x - 0) 2 + (y - 0) 2 x 2 + y 2

= 2 2 = 4

General form:

x 2 + y 2 - 4 = 0

67.

( x - h) 2 + (y - k) 2

= r 2

69.

(x -1) 2 + (y

-(-1)) 2 =1 2

(x -1) 2 + (y +1) 2 =1

General form:

x 2 -2x +1+ y 2 + 2y +1=1

x 2 + y 2 - 2x + 2y

+1= 0

+ 2 y + 1 = 1 x 2 + y 2 - 2 x +

Center = midpoint of (1,2) and (4,2)

Ê 1+ 4 , 2 + 2 ˆ Ê 5 ˆ = Á ˜ =
Ê 1+ 4 , 2 + 2 ˆ
Ê 5
ˆ
= Á
˜
= Á 2 ,2 ˜
Ë
2
2
¯
Ë
¯
Ê 5
ˆ
Radius = distance from
Á 2 ,2 ˜ to (4, 2)
Ë
¯
2
=
Ê
Á 4 - 5 ˜
ˆ
+ (2 -2) 2
Ë 2 ¯
9
=
4 = 2 3
Ê
ˆ
Á x - 5 ˜ 2 + (y -2) 2 = 9
Ë
2 ¯
4
4 = 2 3 Ê ˆ Á x - 5 ˜ 2 + (y -2) 2

( x - h) 2 + (y - k) 2

(x - 0) 2 + (y - 2) 2

x 2 + (y - 2) 2 General form:

= r 2

= 2 2 = 4

x 2 + y 2 - 4y + 4 = 4 x 2 + y 2 - 4y = 0

2) 2 General form: = r 2 = 2 2 = 4 x 2 + y

Section 1.2

Graphs of Equations; Circles

71.

( x - h) 2 + (y - k) 2

= r 2

 

(x - 4) 2 + (y - (-3)) 2 = 5 2 (x - 4) 2 + (y + 3) 2 = 25 General form:

 

x 2 - 8x + 16 + y 2 + 6y + 9

= 25

x 2 + y 2 - 8x + 6y

= 0

 
 

75.

( x - h) 2 + (y -k) 2 = r 2

 
 

(x - 0) 2 + (y -(-3)) 2 = 3 2

 

x 2 +

(

y + 3 ) 2 = 9

 

General form:

 

x 2 + y 2 + 6y + 9 = 9

 
 

x 2 + y 2 + 6y = 0

+ 9 = 9     x 2 + y 2 + 6 y = 0

77.

x

2 + y 2 = 4

x

2 + y 2 = 2 2

(a)

Center : (0,0); Radius = 2

(b)

 
2 (a) Center : (0,0); Radius = 2 (b)   73. ( x - h )

73.

( x - h) 2 + (y -k) 2 = r 2

(x -(-3)) 2 + (y -(-6)) 2 = 6 2

(

x + 3 ) 2 +

(

y + 6 ) 2 = 36

General form:

x 2 + 6x

+ 9+ y 2 + 12y + 36 = 36

x 2 + y 2 + 6x +12 y + 9 = 0

+ 36 = 36 x 2 + y 2 + 6 x + 12 y +

(c)

x-intercepts: y = 0 x 2 + 0 = 4 x = ±2

-2,0 ) , 2,0 y-intercepts: x = 0 0 + y 2 = 4 y = ±2

(

(

)

0,-2 ) , 0,2

(

(

)

Chapter 1

Graphs

79. 2(x - 3) 2 + 2y 2 = 8 (x - 3) 2 +
79.
2(x - 3) 2 + 2y 2 = 8
(x
- 3) 2 +
y 2 = 4
(
x - 3 ) 2 +
y 2 = 2 2
(a)
Center: (3,0); Radius = 2
(b)
81.
x 2 + y 2 + 4x - 4y -1 = 0

x 2 + 4x + y 2 - 4y =1

(x 2 + 4x + 4) + (y 2 - 4y + 4) =1+ 4 + 4

(x + 2) 2 + (y -2) 2 = 3 2

(a)

Center: (–2,2); Radius = 3

(b)

2) 2 = 3 2 (a) Center: (–2,2); Radius = 3 (b) (c) x- intercepts: y

(c)

x-intercepts: y = 0 (x - 3) 2 + 0 = 4

(x - 3) 2 = 4

x - 3 = ±2

x = 5,x =1

1,0 ) , 5,0 y-intercepts: x = 0 9 + y 2 = 4

(

(

y 2 = -5

)

no solution no y - intercepts

(c)

x-intercepts: y = 0 (x + 2) 2 + 4 = 9

(x + 2) 2 = 5

x + 2 = ± 5 x = 5 - 2,x = - 5 -
x + 2 = ±
5
x
=
5 - 2,x = -
5 - 2
(
-
5 -2,0 ) ,
(
5 -2,0
)

y-intercepts: x = 0

4 + (y -2) 2 = 9 (y -2) 2 = 5 y -2 =
4 + (y
-2) 2 = 9
(y
-2) 2 = 5
y -2 = ±
5
y =
5 + 2,y = -
5 + 2
(
0,-
5 + 2 ) , 0,
(
5 + 2

)

Section 1.2

Graphs of Equations; Circles

83.

x 2 + y 2 - 2x + 4y - 4 = 0

(c)

x 2 -2x +

y 2 + 4y = 4

 

(x 2 -2x +1) + (y 2 + 4y + 4) = 4